Capital productivity and investment : their role in profitable airline operations - Morrell, Peter (Cranfield University, 2003)
The aim of the research was to develop and apply improved measures of capital productivity using published airline data, and to evaluate the role of capital investment and productivity in overall airline performance. As well as contributing to total factor productivity, capital productivity is a partial measure, and the investment upon which it is based should improve the productivity of other inputs to the production process, in particular labour and fuel. Productivity ratios require outputs and inputs to be combined and indexed. Index numbers have been developed using weights that are consistent with the underlying economic theory, and also meet various tests (such as reversal and products). Airline passenger, cargo and incidentals were combined using a number of such index number approaches. Capital inputs were estimated using annual lease equivalents which when discounted to the present over the expected future economic lives of the assets resulted gave either balance sheet values adjusted to a common year’s prices, or the total of the market values of individual assets (aircraft).